Opinions of Practitioners Concerning Curricular Requirements of Agricultural Communication Students at the University of Florida - Kimberly J. Sprecker; Rick D. Rudd (Journal of Applied Communications, 1998)
This study identifies opinions of agricultural communication practitioners in Florida concerning knowledge and skills that should be taught to agricultural communication students at the University of Florida. We interviewed 14 practitioners who were on the Board of Directors of the Agriculture Institute of Florida. Practitioners recognized the need for broad-based instruction about agriculture. They said communication skills, however, are more important than subject-area knowledge. Students must be versatile in many communication areas and learn interpersonal networking skills. Desktop publishing and internships are essential, as is training in issues management. Curriculum planners should consider these views when making agricultural communication curriculum decisions.